Athlete Satisfaction and Administrative Effectiveness of Nigerian Universities in Sports Organization - Simon, Kayit Bobai (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
Study is on the relationship between student athlete satisfaction and sports organization effectiveness in Nigeria universities, sports in the universities is essentially for the students and by the students. This means that, the student is the prime beneficiary and also the producer of sports as entertainment in the university. But each time the issue of effectiveness in university sports organization is addressed, consideration is only centered on the programmes, facilities, leadership, coaches and coaching etc. Nothing is mentioned about the student athlete experiences. This deliberate ignorance of the student-athlete's experience leads to the need for this study, to examine the student-athlete satisfaction. To do this, the research design employed for the study was the ex-post-factor research design, which is based on information in existence and cannot be manipulated. The researcher utilize questionnaire as the tool for obtaining the data for the study. The questionnaire constitute of four parts A, B, and C put together as one and was administered to students' athletes from fourteen (14) universities randomly selected from seven (7) stratified Nigerian Universities Games Association (NUGA) zones. Five most popular sports (Football, basketball, athletic, racket game and combat sport) were used, and ten (10) athletes from the above mentioned most popular sports = 10x5 = 50 athletes from each university, = 14x50 = 700 the total number of respondents. The data collected were statistically analyzed, using descriptive, multiple and zero order correlation. The major findings Student-athlete satisfaction is highly related to sports organizational effectiveness. Bot h facets of outcome and processes affects the student athlete satisfaction in the sports organization. The major findings are Students-athlete satisfactions are highly related to sports organizational effectiveness, both facets of outcome and process affects the student satisfaction in the sports organization, individual satisfaction in sports organizations of Nigerian universities and its needs for continued assessment are inseparable in Nigerian university, coaches and sports administrators needed cannot produce the entertainment from sports organizations. Students-athlete satisfactions and its needs for continued assessment are inseparable in Nigerian university sorts organization. Keywords: Athletic satisfaction, sport administration achieving effectiveness sport organization.